Early Post-Operative Acute Myocardial Infarction in Kidney Transplant Recipients: Incidence, Risk Factors, and Outcomes. (July 2018) - Gupta, Nikita; Deeb, Maya; Overgaard, Christopher; Li, Yanhong; Famure, Olusegun; Kim, Joseph S.
Abstract : Introduction: Kidney transplantation continues to remain the gold standard clinical treatment for patients with end stage renal disease (ESRD). However, cardiovascular disease presents a significant cause of morbidity and mortality. The epidemiology of acute myocardial infarctions in the early post-operative period after kidney transplantation has not been well characterized. This study sought to examine the incidence, risk factors, and clinical outcomes of early post-operative acute myocardial infarctions or EAMI (i.e., occurring within 3-months post-transplant) in a contemporary cohort of kidney transplant recipients. Methodology: A total of 1976 patients who underwent kidney transplantation at our center from 1 Jan 2000 to 30 June 2016 (minimum follow-up time: 6 months) were included. A nested case-control design was used to study EAMI risk factors using a conditional logistic regression model. EAMI cases were adjudicated by a single cardiologist using the consensus definition set by the American Heart Association. Each case was matched to 5 controls on follow-up time, transplant year, and donor type. To assess the association of EAMI with clinical outcomes such as graft loss, death with function, and hospital readmission, a Cox proportional hazards model was fitted to the total study cohort. Results: A total of 74 kidney transplant recipients had an EAMI episode within the first 3 months post-transplant, with just over half of these cases (39) occurring within the first 3 days post-transplant. Based on a univariable conditional logistic regression model, the recipient risk factors found to predict EAMI included age at transplant (OR 1.05, p < 0.001), history of diabetes mellitus (OR 2.82, p < 0.001), and recipient history of coronary artery disease (OR 5.72, p < 0.001). After adjustment, recipient history of coronary artery disease was found to be the only independent predictor of EAMI (OR 3.76, p < 0.001). Patients who experienced an EAMI were at an increased risk for total graft failure (HR 3.25, p < 0.001), death-censored graft failure (HR 2.46, p = 0.002), and death with function (HR 4.00, p < 0.001). The mean estimated glomerular filtration rate was not found to be significantly different at 6 months, 12 months, and 24 months post-transplant in adjusted analyses. Finally, patients experiencing an EAMI episode had a 79% higher risk of hospital readmission over follow-up (p < 0.001). Conclusion: While the incidence of EAMI in kidney transplant recipients is relatively low, these data show that EAMI has profound long-term effects on patient morbidity and mortality. Further, this study shows that EAMI patients are at an increased risk for hospital readmissions, indicating implications of EAMI at both the patient and health system levels.